Ectodermal Dysplasia with Anodontia in both Deciduous and Permanent Dentition: A Case Report - Bhetwal, Babita (Hasanuddin University, 2023)
Ectodermal dysplasia is typically an inherited X-linked recessive trait, characterized by a variety of congenital defects in structure of ectodermal origin which includes skin, hair, teeth, nails and sweat glands. Hypodontia or anodontia of primary or permanent dentition is the most common oral findings. A 22 years old man has been reported to the Department of Prosthodontics and Maxillofacial Prosthesis Kathmandu Medical College and Teaching Hospital, Duwakot Bhaktapur with chief complaint of complete missing of upper and lower teeth since childhood.Â He has typical features of hypohidrotic ectodermal dysplasia; diffusely sparse hairs, reduced eyelash and eyebrows hair, midface hypoplasia, protuberant lips, satyr-like ears and prominent forehead. We present the features, diagnosis and treatment plant for the patient in this case report.